2022
DOI: 10.1038/s41467-022-32297-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of companion galaxies around hot dust-obscured hyper-luminous galaxy W0410-0913

Abstract: The phase transition between galaxies and quasars is often identified with the rare population of hyper-luminous, hot dust-obscured galaxies. Galaxy formation models predict these systems to grow via mergers, that can deliver large amounts of gas toward their centers, induce intense bursts of star formation and feed their supermassive black holes. Here we report the detection of 24 galaxies emitting Lyman-α emission on projected physical scales of about 400 kpc around the hyper-luminous hot dust-obscured galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
(120 reference statements)
2
10
0
Order By: Relevance
“…At high redshift, there are now observations of a handful of other protoclusters sharing three key properties-the large stellar mass of the central galaxy and a large number of nearby companions and their high velocity dispersion-with J1652 (Shi et al 2021;Ginolfi et al 2022). For example, a powerful radio-loud AGN, PKS 1138-262, at z ∼ 2.2 is hosted by a massive galaxy with M * ∼ 10 12 M e (Seymour et al 2007;Hatch et al 2009), also known as the Spiderweb galaxy.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…At high redshift, there are now observations of a handful of other protoclusters sharing three key properties-the large stellar mass of the central galaxy and a large number of nearby companions and their high velocity dispersion-with J1652 (Shi et al 2021;Ginolfi et al 2022). For example, a powerful radio-loud AGN, PKS 1138-262, at z ∼ 2.2 is hosted by a massive galaxy with M * ∼ 10 12 M e (Seymour et al 2007;Hatch et al 2009), also known as the Spiderweb galaxy.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…To this end, we applied two line-finding algorithms to both the real and jack-knifed data sets: (1) the python-based line-finding algorithm used by Béthermin et al (2020) (see their Sect. 6) and Ginolfi et al (2022) and (2) the algorithm Findclumps, described in Walter et al (2016), which is available as part of the python library, Interferopy (Boogaard et al 2021) 3 . For the real data, we used the dirty image cubes and replicated the noise properties in the jack-knifed cubes as described in Sect.…”
Section: Likelihood Of Detecting Two Correlated Noise Peaksmentioning
confidence: 99%
“…Recently, Ginolfi et al (2022) studied the environment of W0410-0913, a Hot DOG at z = 3.631, using VLT/MUSE observations, and also concluded that this Hot DOG lives in a dense Fig. 8.…”
Section: Overdensities Around Hot Dogsmentioning
confidence: 99%
“…Multiwavelength observations of Hot DOGs have statistically shown that these objects are likely to live in dense environments (Jones et al 2014;Assef et al 2015;Penney et al 2019). More recently, Luo et al (2022) found an overdensity of distant red galaxies (DRGs) around a Hot DOG at z = 2.3, while Ginolfi et al (2022) revealed an overdensity of LAEs in the environment of a z = 3.6 Hot DOG with VLT/MUSE observations. All of this evidence suggests that Hot DOGs exist in overdense regions of the Universe, where significant gas accretion can be maintained and mergers could lead to large-scale obscuration.…”
Section: Introductionmentioning
confidence: 99%